2013
DOI: 10.3748/wjg.v19.i10.1602
|View full text |Cite
|
Sign up to set email alerts
|

Rates and impact of hepatitis on human immunodeficiency virus infection in a large African cohort

Abstract: High rates of HBV and HCV infections were found in this HIV cohort. CD4 recovery was significantly diminished in patients with HBV co-infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 27 publications
6
32
1
Order By: Relevance
“…On the other hand, higher baseline HIV RNA in HIV/HBV-coinfected participants has been documented [13]. In this study, similar to studies conducted in South Africa and Kenya, there was no difference in HIV viral load suppression between the 2 groups [1, 15, 22].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, higher baseline HIV RNA in HIV/HBV-coinfected participants has been documented [13]. In this study, similar to studies conducted in South Africa and Kenya, there was no difference in HIV viral load suppression between the 2 groups [1, 15, 22].…”
Section: Discussionsupporting
confidence: 80%
“…The results obtained in the study were similar to those obtained by Ladep et al in Nigeria, where the rate of HBV/HIV coinfection was 17.8% using HBsAg as a marker [10]. Also, Utsumi et al [11] in Indonesia and Geretti et al [12] in China reported results consistent with our findings (15.3%, and 16.7%, respectively), using ELISA to detect HBsAg.…”
Section: Discussionsupporting
confidence: 82%
“…HCV infection is relatively common in HIV-infected people, and its management is especially difficult in resource-limited areas such as sub-Saharan African countries [9]. The reported prevalence of HCV-HIV co-infection in this part of the continent is highly variable [10][11][12][13][14] and is probably underestimated because it is often based on serology. Indeed, HCV RNA was detected in six HIV-infected donors who were HCV seronegative at screening.…”
Section: Discussionmentioning
confidence: 99%